Preparation method of Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide
By loading amino acid-functionalized ionic liquids onto the Al-MIL-53 framework, Al-MIL-53 composite materials were prepared, solving the problems of low adsorption selectivity and slow diffusion rate. This enabled efficient synergistic adsorption of carbon dioxide and hydrogen sulfide, improving biogas purification efficiency and equipment stability.
Patent Information
- Application Number
- CN202511071769.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-01
- Publication Date
- 2025-11-21
AI Technical Summary
Existing Al-MIL-53 materials exhibit low adsorption selectivity in biogas desulfurization and decarbonization, and the slow diffusion rate of ionic liquids during gas adsorption leads to equipment wear and affects the calorific value of syngas.
By loading amino acid-functionalized ionic liquids onto the Al-MIL-53 framework, Al-MIL-53 composite materials were prepared, combining the advantages of both to improve the adsorption selectivity and stability of the material.
It achieves efficient synergistic adsorption of carbon dioxide and hydrogen sulfide, with high stability and large specific surface area, extending equipment life, reducing operation and maintenance costs, and providing an efficient and green biogas purification solution.
Smart Images

Figure CN120984240A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of biogas desulfurization and decarburization purification technology, and particularly relates to a preparation method of an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide. BACKGROUND
[0002] With the acceleration of industrialization and urbanization, the "greenhouse effect" is becoming increasingly serious. Controlling and reducing the CO2 emissions, one of the main greenhouse gases, has attracted global attention. The combustion of fossil fuels releases a large amount of carbon dioxide, which is one of the main reasons for global climate change. New energy such as biomass energy, solar energy, nuclear energy has attracted widespread attention because it can reduce fossil fuel consumption and greenhouse gas emissions. Biogas formed by fermentation has four characteristics of clean, efficient, safe and renewable. Its composition is mainly CH4(50-70vol%), CO2(30-50vol%) and hydrogen sulfide gas. The presence of CO2 and H2S not only causes equipment wear and tear, but also greatly affects the heating value of the synthesis gas. By upgrading the biogas, its heating value can be increased from 21.5 MJ / m 3 to 36 MJ / m 3 . Therefore, it is necessary to use a stable and environmentally friendly adsorbent with low regeneration energy consumption to upgrade the synthesis gas.
[0003] Ionic liquids are molten salt compounds composed of organic cations and inorganic or organic anions, which are in liquid state at room temperature or near room temperature (usually below 100℃). They have the characteristics of structure controllability, high selectivity and low regeneration energy consumption, and have been preliminarily applied in the field of gas adsorption. However, due to the high viscosity of ionic liquids, the gas diffusion rate is slow, and the gas adsorption time is prolonged.
[0004] Metal-organic framework compound Al-MIL-53 is a new type of porous material, which takes Al 3+ ion as the central metal ion and 1,4-benzenedicarboxylic acid as the linker to form a network structure. It has the characteristics of diverse framework structure, high porosity, large specific surface area and high stability, and shows good application prospect in the fields of gas storage and separation. However, the low adsorption selectivity of Al-MIL-53 limits its application in the field of biogas desulfurization and decarburization.
[0005] Based on the above, the present application proposes a preparation method of loading ionic liquid on Al-MIL-53, and applies it to the field of biogas purification technology. SUMMARY
[0006] The Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide is prepared by the method.
[0007] To achieve the above object, the technical scheme adopted by the present application is:
[0008] Firstly, a method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide comprises the following steps:
[0009] After the amino acid is dissolved in water and the pH is adjusted to above the isoelectric point, a tetrabutylammonium chloride-containing methanol solution is added, and stirring is performed at room temperature for 6-8 hours; after centrifugation to remove NaCl, an ionic liquid is obtained.
[0010] The ionic liquid and Al-MIL-53 are uniformly mixed, and vacuum drying is performed to obtain the Al-MIL-53 composite material.
[0011] Further, the molar ratio of the ionic liquid to Al-MIL-53 is 1:4-7.
[0012] Further, the method for preparing Al-MIL-53 comprises:
[0013] Aluminum nitrate nonahydrate and terephthalic acid are sequentially added to dimethylformamide, and after stirring to form a transparent solution, the solution is placed in a reaction kettle, heated at 200-230 DEG C for 54-72 hours; the obtained milky white gel-like crystals are washed with deionized water and anhydrous ethanol alternately for several times, and finally dried and placed in a muffle furnace at 280-300 DEG C for calcination to obtain Al-MIL-53.
[0014] Further, the molar ratio of the aluminum nitrate nonahydrate to terephthalic acid is 1:0.5-2.
[0015] Further, in the method for preparing Al-MIL-53, the drying is performed at 90-120 DEG C for 10-12 hours.
[0016] Further, the amino acid is one or more of glutamic acid, glycine, aspartic acid in any proportion.
[0017] Further, the vacuum drying is performed at 50-80 DEG C for 1-3 hours.
[0018] The ionic liquid is loaded on the Al-MIL-53, which can not only avoid the problem of high viscosity in the ionic liquid adsorption process, but also improve the adsorption selectivity of the material, and provide more carbon dioxide / hydrogen sulfide adsorption sites. Therefore, the material has the advantages of high stability, large specific surface area, high adsorption selectivity, and the like, thereby realizing the effective removal of carbon dioxide and hydrogen sulfide.
[0019] The second aspect: the Al-MIL-53 composite material prepared by the above preparation method.
[0020] The third aspect: the application of the Al-MIL-53 composite material in capturing carbon dioxide and hydrogen sulfide in biogas to prepare high-value methane.
[0021] Further, the biogas is introduced into a fixed bed containing the Al-MIL-53 composite material to prepare high-value methane.
[0022] Compared with the prior art, the present application has the following advantages:
[0023] 1. The Al-MIL-53 composite material of the present application combines the structure adjustability of MOF materials with the functional design of amino acid ionic liquids by compounding the amino acid functional ionic liquid with the Al-MIL-53 framework, realizing the efficient and synergistic adsorption of CO2 and H2S.
[0024] 2. The present application breaks through the bottleneck of traditional adsorbents in capacity, selectivity and stability, and provides an efficient and green solution for biogas purification and industrial flue gas treatment, which has significant environmental and economic benefits.
[0025] 3. The ionic liquid can inhibit the corrosion of H2S on metal pipelines, prolong the service life of equipment, and reduce the operation and maintenance cost by 30%. BRIEF DESCRIPTION OF DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiment description. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without creative labor.
[0027] Figure 1 A flowchart of a preparation method of an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide is provided for the embodiments of the present application;
[0028] Figure 2 A flowchart of another preparation method of an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide is provided for the embodiments of the present application;
[0029] Figure 3 Flow chart for application of Al-MIL-53 composite material provided by the embodiments of the present application to capture carbon dioxide and hydrogen sulfide in biogas to prepare high-value methane. DETAILED DESCRIPTION
[0030] The present application will be further described in conjunction with the embodiments and drawings, but the embodiments of the present application are not limited thereto. In the embodiments of the present application, the specific conditions not mentioned are carried out according to the conventional conditions or the conditions recommended by the manufacturers. The raw materials, reagents and the like not mentioned by the manufacturers are all conventional products that can be purchased in the market.
[0031] A preparation method of an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide according to the present application, see Figure 1 and Figure 2 , comprises the following steps:
[0032] (1) Dissolve 0.1 mol of amino acid in water, adjust the pH to above the isoelectric point, then add 50 ml of methanol solution containing 0.1-0.15 mol of tetrabutylammonium chloride, stir at room temperature for 6-8 hours, remove NaCl by centrifugation, and obtain an ionic liquid.
[0033] (2) Add aluminum nitrate nonahydrate and terephthalic acid to 65 ml of dimethylformamide in a molar ratio of 1:0.5-2, stir magnetically to form a transparent solution, then place the solution in a 100 mL polytetrafluoroethylene-lined stainless steel high-pressure reaction kettle, heat at 200-230°C for 54-72 h; wash the obtained milky white gel-like crystals with deionized water and anhydrous ethanol alternately for 5 times, finally dry at high temperature, i.e. dry at 90-120°C for 10-12 h, then place in a muffle furnace at 280-300°C and calcine for 24 h, to obtain an Al-MIL-53 adsorbent.
[0034] (3) Mix the ionic liquid obtained in step (1) and the Al-MIL-53 adsorbent obtained in step (2) uniformly in a molar ratio of 1:4-7, vacuum dry, i.e. dry at 50-80°C for 1-3 h, to obtain an Al-MIL-53 composite material.
[0035] In an embodiment, the amino acid is one or more of glutamic acid, glycine, aspartic acid in any proportion.
[0036] Example 1:
[0037] A preparation method of an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide, comprising the following steps:
[0038] (1) Preparation of ionic liquid:
[0039] 0.72 g glutamic acid was dissolved in 100 ml deionized water, the pH was adjusted to 3.5, 50 ml methanol solution containing 1.39 g tetrabutylammonium chloride was added, and stirred at room temperature for 7 hours. After removing NaCl by centrifugation, an ionic liquid was obtained.
[0040] (2) Preparation of Al-MIL-53 adsorbent:
[0041] 3.75 g aluminum nitrate nonahydrate and 1.66 g terephthalic acid were sequentially added to 65 ml dimethylformamide, and after magnetic stirring to form a transparent solution, the solution was placed in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, heated at 220°C for 72 h. The obtained milky white gel-like crystals were washed with deionized water and anhydrous ethanol alternately for 5 times, and finally dried at 90°C for 12 h and then calcined in a muffle furnace at 300°C for 24 h to obtain Al-MIL-53 adsorbent.
[0042] (3) Preparation of Al-MIL-53 composite:
[0043] The ionic liquid obtained in step 2 and the Al-MIL-53 adsorbent obtained in step 3 were mixed uniformly at a molar ratio of 1:5, and vacuum dried at 60°C for 2 h to obtain an Al-MIL-53 composite.
[0044] (4) Carbon dioxide and hydrogen sulfide mixed gas were passed into a fixed bed containing the Al-MIL-53 composite, the adsorption temperature was 50°C, the gas flow rate was 100 ml / min, and the adsorption time was 30 min. When the inlet and outlet gas concentrations were unchanged, it was considered that the adsorption equilibrium was reached. It was found by experiment that the adsorption capacity of the composite was 0.35 mmol / g more than that of the ionic liquid.
[0045] Example 2:
[0046] A preparation method of an Al-MIL-53 composite for capturing carbon dioxide / hydrogen sulfide, comprising the following steps:
[0047] (1) Preparation of ionic liquid:
[0048] 0.72 g glutamic acid was dissolved in 100 ml deionized water, the pH was adjusted to 3.5, 50 ml methanol solution containing 1.53 g tetrabutylammonium chloride was added, and stirred at room temperature for 7 hours. After removing NaCl by centrifugation, an ionic liquid was obtained.
[0049] (2) Preparation of Al-MIL-53 adsorbent:
[0050] Al-MIL-53 adsorbent was obtained by adding 3.75 g of aluminum nitrate nonahydrate and 1.10 g of terephthalic acid into 65 ml of dimethylformamide in sequence, stirring magnetically to form a transparent solution, placing the solution in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and heating at 220 °C for 72 h. The obtained milky white gel-like crystals were washed with deionized water and anhydrous ethanol alternately for 5 times, and finally dried at 90 °C for 12 h and then calcined in a muffle furnace at 300 °C for 24 h.
[0051] (3) Preparation of Al-MIL-53 composite material:
[0052] The ion liquid obtained in step 2 and the Al-MIL-53 adsorbent obtained in step 3 were mixed uniformly at a molar ratio of 1:5, and vacuum dried at 60 °C for 2 h to obtain the Al-MIL-53 composite material.
[0053] (4) Carbon dioxide and hydrogen sulfide mixed gas were passed into a fixed bed containing the Al-MIL-53 composite material, the adsorption temperature was 50 °C, the gas flow rate was 100 ml / min, and the adsorption time was 30 min. When the inlet and outlet gas concentrations were unchanged, it was considered that the adsorption equilibrium was reached.
[0054] Example 3:
[0055] A method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide, comprising the following steps:
[0056] (1) Preparation of ion liquid:
[0057] 0.72 g of glutamic acid was dissolved in 100 ml of deionized water, the pH was adjusted to 3.5, 50 ml of methanol solution containing 1.6 g of tetrabutylammonium chloride was added, and stirring was performed at room temperature for 7 hours. After centrifugation to remove NaCl, an ion liquid was obtained.
[0058] (2) Preparation of Al-MIL-53 adsorbent:
[0059] Al-MIL-53 adsorbent was obtained by adding 3.75 g of aluminum nitrate nonahydrate and 1.10 g of terephthalic acid into 65 ml of dimethylformamide in sequence, stirring magnetically to form a transparent solution, placing the solution in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and heating at 220 °C for 72 h. The obtained milky white gel-like crystals were washed with deionized water and anhydrous ethanol alternately for 5 times, and finally dried at 90 °C for 12 h and then calcined in a muffle furnace at 300 °C for 24 h.
[0060] (3) Preparation of Al-MIL-53 composite material:
[0061] The ionic liquid prepared in step 2 and the Al-MIL-53 adsorbent prepared in step 3 are mixed uniformly at a molar ratio of 1:5, and the Al-MIL-53 composite material is obtained after vacuum drying at 60°C for 2h.
[0062] (4) The mixed gas of carbon dioxide and hydrogen sulfide is passed into the fixed bed containing the Al-MIL-53 composite material, the adsorption temperature is 50°C, the gas flow rate is 100ml / min, and the adsorption time is 30min. When the inlet and outlet gas concentrations remain unchanged, it is considered that the adsorption equilibrium is reached.
[0063] Example 4:
[0064] A preparation method of an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide, comprising the following steps:
[0065] (1) Preparation of ionic liquid:
[0066] 0.72g glutamic acid is dissolved in 100ml deionized water, the pH is adjusted to 3.5, 50ml methanol solution containing 1.8g tetrabutylammonium chloride is added, and stirring is carried out at room temperature for 7h. After centrifugation to remove NaCl, the ionic liquid is obtained.
[0067] (2) Preparation of Al-MIL-53 adsorbent:
[0068] 3.75g aluminum nitrate nonahydrate and 0.83g terephthalic acid are sequentially added to 65ml dimethylformamide, and after magnetic stirring to form a transparent solution, the solution is placed in a 100mL polytetrafluoroethylene-lined stainless steel high-pressure reaction kettle, heated at 220°C for 72h. The obtained milky white gel-like crystals are washed with deionized water and anhydrous ethanol alternately for 5 times, and finally dried at 90°C for 12h and then calcined in a muffle furnace at 300°C for 24h to obtain the Al-MIL-53 adsorbent.
[0069] (3) Preparation of Al-MIL-53 composite material:
[0070] The ionic liquid prepared in step 2 and the Al-MIL-53 adsorbent prepared in step 3 are mixed uniformly at a molar ratio of 1:5, and the Al-MIL-53 composite material is obtained after vacuum drying at 60°C for 2h.
[0071] (4) The mixed gas of carbon dioxide and hydrogen sulfide is passed into the fixed bed containing the Al-MIL-53 composite material, the adsorption temperature is 50°C, the gas flow rate is 100ml / min, and the adsorption time is 30min. When the inlet and outlet gas concentrations remain unchanged, it is considered that the adsorption equilibrium is reached.
[0072] Example 5:
[0073] A preparation method of an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide, comprising the following steps:
[0074] (1) Preparation of an ionic liquid:
[0075] 0.72 g of glutamic acid was dissolved in 100 ml of deionized water, the pH was adjusted to 3.5, 50 ml of a methanol solution containing 1.95 g of tetrabutylammonium chloride was added, and stirring was performed at room temperature for 7 hours. After centrifugation to remove NaCl, an ionic liquid was obtained.
[0076] (2) Preparation of an Al-MIL-53 adsorbent:
[0077] 3.75 g of aluminum nitrate nonahydrate and 2.49 g of terephthalic acid were sequentially added to 65 ml of dimethylformamide, and after magnetic stirring to form a transparent solution, the solution was placed in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, heated at 220°C for 72 h. The obtained milky white gel-like crystals were washed with deionized water and anhydrous ethanol alternately for 5 times, and finally dried at 90°C for 12 h and then calcined in a muffle furnace at 300°C for 24 h to obtain an Al-MIL-53 adsorbent.
[0078] (3) Preparation of an Al-MIL-53 composite material:
[0079] The ionic liquid obtained in step 2 and the Al-MIL-53 adsorbent obtained in step 3 were mixed uniformly at a molar ratio of 1:5, and vacuum dried at 60°C for 2 h to obtain an Al-MIL-53 composite material.
[0080] (4) A mixture of carbon dioxide and hydrogen sulfide was passed into a fixed bed containing the Al-MIL-53 composite material, the adsorption temperature was 50°C, the gas flow rate was 100 ml / min, and the adsorption time was 30 min. When the inlet and outlet gas concentrations were unchanged, it was considered that the adsorption equilibrium was reached.
[0081] Application of the Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide.
[0082] The Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide prepared in Example 2, the Al-MIL-53, and the ionic liquid were used to capture carbon dioxide and hydrogen sulfide in biogas to prepare high-value methane, and a comparison was made. See Figure 3 , specifically:
[0083] The Al-MIL-53 composite material prepared in Example 2 and the ionic liquid were respectively put into a fixed bed, and the air in the device was purged by using nitrogen at a gas flow rate of 50 ml / min for 30 min. The nitrogen valve was closed, and biogas (39.9% carbon dioxide, 0.1% hydrogen sulfide and 60% methane) was introduced. The reaction conditions were as follows: adsorption temperature 50 DEG C, gas flow rate 100 ml / min, and adsorption time 30 min. Every 4 min, a certain amount of gas was collected at the outlet, and the gas components were detected by using a gas chromatograph until the gas concentrations at the inlet and outlet were constant. The gas components are shown in Table 1.
[0084] Table 1: Gas components
[0085] Methane Carbon dioxide Hydrogen sulfide Initial concentration 60% 39.90% 0.10% After adsorption Example 2 >95% <4% <0.005% After adsorption Al-MIL-53 >92% <7% <0.02% After absorption of ionic liquid >90% <9% <0.01%
[0086] It is proved by experiments that the Al-MIL-53 composite material prepared in the application has good effects on capturing carbon dioxide and hydrogen sulfide in biogas, and has low cost, no pollution and good application prospect in the field of biogas desulfurization and decarburization purification technology.
[0087] The above is only the preferred embodiment of the application, and it should be pointed out that the above preferred embodiment should not be regarded as a limitation of the application, and the protection scope of the application should be limited by the scope defined in the claims. For ordinary skilled persons in the art, several improvements and refinements can be made without departing from the spirit and scope of the application, and these improvements and refinements should also be regarded as the protection scope of the application.
Claims
1. A method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide, characterized in that, include: The amino acids were dissolved in water, the pH was adjusted to above the isoelectric point, and then a methanol solution containing tetrabutylammonium chloride was added. The mixture was stirred at room temperature for 6–8 hours, and the NaCl was removed by centrifugation to obtain the ionic liquid. The ionic liquid and Al-MIL-53 were mixed evenly and then dried under vacuum to obtain the Al-MIL-53 composite material.
2. The method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide according to claim 1, characterized in that, The molar ratio of the ionic liquid to Al-MIL-53 is 1:4 to 7.
3. The method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide according to claim 1, characterized in that, The preparation methods of Al-MIL-53 include: Aluminum nitrate nonahydrate and terephthalic acid were added sequentially to dimethylformamide and stirred until a transparent solution was obtained. The solution was then placed in a reaction vessel and heated at 200–230 °C for 54–72 h. The resulting milky white gel-like crystals were washed several times with deionized water and anhydrous ethanol, and finally dried and calcined in a muffle furnace at 280–300 °C to obtain Al-MIL-53.
4. The method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide according to claim 3, characterized in that, The molar ratio of aluminum nitrate nonahydrate to terephthalic acid is 1:0.5-2.
5. The method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide according to claim 3, characterized in that, In the preparation method of Al-MIL-53, the drying is performed at 90-120°C for 10-12 hours.
6. The method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide according to claim 1, characterized in that, The amino acid is one or more of glutamic acid, glycine, and aspartic acid in any proportion.
7. The method for preparing an Al-MIL-53 composite material for capturing carbon dioxide / hydrogen sulfide according to claim 1, characterized in that, The vacuum drying is performed at 50–80°C for 1–3 hours.
8. The Al-MIL-53 composite material prepared by the preparation method according to any one of claims 1-7.
9. The application of the Al-MIL-53 composite material according to claim 8 in the capture of carbon dioxide and hydrogen sulfide from biogas to produce high-value methane.
10. The application according to claim 9, characterized in that, Biogas is introduced into a fixed bed containing Al-MIL-53 composite material to prepare high-value methane.